PENERAPAN PEMBELAJARAN KONTEKSTUAL PADA MATA PELAJARAN SENI BUDAYA DENGAN MENGGUNAKAN LAGU-LAGU NASIONAL - Prihantoro, Puthut; Fauziati, Endang; Haryanto, Sigit (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Recent phenomena indicate a decline in students’ interest in appreciating cultural arts, particularly through national songs, due to the dominance of foreign popular culture and the lack of learning innovation in schools. This situation reduces the internalization of national values and weakens student engagement in cultural arts education. This study aims to analyze the application of Contextual Teaching and Learning (CTL) in cultural arts subjects by employing national songs as a learning medium. A descriptive qualitative design was used with one cultural arts teacher and 32 grade XI students of SMA Negeri 1 Colomadu as research participants. Data were collected through classroom observations, in-depth interviews, and document analysis, then analyzed using a thematic approach to identify patterns, relevance, and effectiveness. The findings reveal that CTL based on national songs successfully increases students’ learning motivation, strengthens their emotional connection with the material, and fosters awareness of national values. Teachers also reported greater creativity in designing meaningful and contextual strategies. The study concludes that integrating CTL with national songs not only improves cultural arts learning but also revitalizes students’ character building and national identity. The contribution of this research lies in enriching the theoretical discourse on CTL integration in cultural arts and offering a practical model that addresses the challenges of globalization while strengthening love for the homeland.